5-Hydroxymethylfurfural Alleviates Inflammatory Lung Injury by Inhibiting Endoplasmic Reticulum Stress and NLRP3 Inflammasome Activation - Zhang, Hang; Jiang, Zheyi; Shen, Chuanbin; Zou, Han; Zhang, Zhiping; Wang, Kaitao; Bai, Renren; Kang, Yanhua; Ye, Xiang-Yang; Xie, Tian (Frontiers in Cell and Developmental Biology, 2021)
5-Hydroxymethylfurfural (5-HMF) is a common reaction product during heat processing and the preparation of many types of foods and Traditional Chinese Medicines. This study aims to figure out the protective effect of 5-HMF treatment on endotoxin-induced inflammatory acute lung injury (ALI) and the underlying mechanism. Our findings indicate that 5-HMF attenuated LPS-induced ALI in mice, which manifested in the reduction of the alveolar structure destruction, the infiltration of neutrophils, and the release of the inflammatory cytokines. Meanwhile, in vitro experiments revealed that activation of macrophages and human monocytes in response to lipopolysaccharide (LPS) was remarkably suppressed by 5-HMF through inhibiting LPS-induced activation of NF-κB-dependent signaling events. In addition, 5-HMF inhibited NLRP3 inflammasome activation and endoplasmic reticulum (ER) stress in macrophages. The activation of 5-HMF to inhibit NLRP3 inflammasome was ameliorated by overexpression of ATF4 or CHOP, indicating that ER stress is involved in the negative regulation of 5-HMF on NLRP3 inflammasome-mediated inflammation. The further study showed that 5-HMF-driven amelioration of pulmonary dysfunction were reversed by the ER stress inducer tunicamycin in vivo, which confirmed the protective effects of 5-HMF on ALI by modulation of ER stress. In conclusion, our findings elucidate the anti-inflammatory and protective efficacy of 5-HMF in LPS-induced acute lung injury, and also demonstrate the key mechanism of its action against NLRP3 inflammasome-related inflammatory disorders via the inhibition of ER stress.